Phonological Awareness in Students with Dyslexia and Intellectual Disabilities - Ranti Novianti; Fadly Halim Hutasuhut; Sinta Yuni Susilawati; Yoga Budhi Santoso; Ana Fatimatuzzahra; Ristria Ningrum (Universitas Sultan Ageng Tirtayasa, 2026)
Students with dyslexia and students with intellectual disabilities often experience reading difficulties. Numerous studies have suggested that these difficulties are closely related to deficits in phonological awareness. However, comprehensive studies comparing the phonological profiles of both groups within the context of Indonesian orthography remain very limited. This study aimed to describe the phonological awareness abilities of dyslexic learners and students with mild intellectual disabilities in beginning reading activities. The study employed a descriptive comparative approach using a small-scale multiple case study design. The participants consisted of four participants with dyslexia from inclusive elementary schools in Bandung and four students with mild intellectual disabilities from special schools in Malang. Data were collected through phonological and beginning reading tests. Although that both groups experienced difficulties in manipulating speech sounds, particularly in blending phonemes, segmenting words into phonemes, and reading words with more complex patterns such as consonant-vowel-consonant (CVC) structures. Among students with dyslexia, the difficulties were more apparent in word reading accuracy. By comparison, students with intellectual disabilities demonstrated broader challenges related to understanding instructions, attention, verbal memory, and language processing.